Sculpting the middle class : history, masculinity and the Amar chitra katha in India - Sreenivas, Deepa (Routledge, Taylor & Francis Group, 2010)
This book is an analysis of the Amar Chitra Katha genre, historical comic-books that capture and promote a middle class masculine identity, as culture became the new site for right-wing hegemonic politics in India over the last 4 decades of the 20th century.